Effect Of Palm Oil (Elias Guinensis) Leaf Standardized Extract On Progression Of Renal Dysfunction And Arterial Stiffness In Normal And High Fat Diet Fed Sprague Dawley Rats With Induced Nephrotoxicity - Ibraheem, Zaid Osamah (2011)
Saturated free fatty acids (SAFFAs) trigger their deleterious effects through inducing the intracellular inflammatory pathway related to insulin resistance. This results in a constellation of biomedical disorders known as metabolic syndrome. Gentamicin is a widely used aminoglycoside antibiotic. Its nephrotoxic action is characterized by both proximal convoluted tubules and glomerular membrane damage. The mechanism of nephrotoxicity is closely related to oxidative stress and free radicals generation.